Peluang, Tantangan, dan Harapan Otonomi Daerah Bidang Pendidikan Islam di Indonesia - Muhammad Khaidir Kahfi Natsir (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
This paper discusses the implementation of regional autonomy and its impact on Islamic education in Indonesia, focusing on the challenges and opportunities faced. Although educational decentralization is considered a strategic step to improve the quality of education, there are various obstacles that must be addressed, including the development of regional capacity, the availability of educational resources, and effective leadership. This study aims to explore how regional autonomy can provide flexibility in educational management while identifying issues arising from the lack of coordination between regional and central governments, especially in the management of Islamic educational institutions. The method used is a normative legal approach with descriptive analysis. The research findings indicate that despite efforts to enhance Islamic education, there remain significant gaps in funding, facilities, and educational quality compared to general education. The conclusion drawn is the need for more inclusive and responsive policy reforms to local diversity, as well as the importance of collaboration among government, society, and educational institutions to create a more equitable and quality education system.